2011
DOI: 10.3354/meps09080
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal movement patterns of a multi-species coastal reef shark aggregation

Abstract: The quantification of spatial and temporal movement patterns of coral reef sharks is important to understand their role in reef communities and to aid the design of conservation strategies for this predatory guild. We observed 4 species of reef sharks aggregating in an inshore bay in the north of Western Australia for over 2 yr, using acoustic telemetry and visual censuses to examine how they partitioned this site in space and time. We fitted 58 sharks with acoustic transmitters: Carcharhinus melanopterus (36)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
89
2
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 45 publications
7
89
2
3
Order By: Relevance
“…Hobson 1963;Randall 1977;McKibben and Nelson 1986;Robbins et al 2006;Papastamatiou et al 2009b) as well as general movement patterns (e.g. Heupel et al 2010;Speed et al 2010Speed et al , 2011Barnett et al 2012;Vianna et was not observed on reef flats, and density estimates for this species were higher on the reef slope compared to the back reef. This result is comparable with previous research, which observed C. amblyrhynchos in greater numbers on outer reef slopes that are associated with strong currents (McKibben and Nelson 1986;Wetherbee et al 1997;Papastamatiou et al 2006;Field et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Hobson 1963;Randall 1977;McKibben and Nelson 1986;Robbins et al 2006;Papastamatiou et al 2009b) as well as general movement patterns (e.g. Heupel et al 2010;Speed et al 2010Speed et al , 2011Barnett et al 2012;Vianna et was not observed on reef flats, and density estimates for this species were higher on the reef slope compared to the back reef. This result is comparable with previous research, which observed C. amblyrhynchos in greater numbers on outer reef slopes that are associated with strong currents (McKibben and Nelson 1986;Wetherbee et al 1997;Papastamatiou et al 2006;Field et al 2011).…”
Section: Discussionmentioning
confidence: 92%
“…Long-term movement and residency patterns of reef sharks can also provide insight into the reproductive behaviour of a species. For example, movement information can be used to identify shark aggregations (Economakis and Lobel 1998;Speed et al 2011), size/sex segregation patterns (Knip et al 2012a;Chin et al 2013a, b), and potential mating and parturition behaviours (Papastamatiou et al 2013;Werry et al 2014), which ultimately have an important conservation value for a species. The present study examined the longterm residency patterns and space use of grey reef sharks C. amblyrhynchos in the central GBR.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes autores han planteado alta fidelidad del aletiblanco a los lugares de asentamiento y agregación (Musick, Harbin & Compagno, 2004;Speed et al, 2011;Whitney et al, 2012). En particular, Speed et al (2011) sugieren que esta fidelidad se presenta a través del tiempo, e incluso en grandes sistemas arrecifales continuos, proponiendo que ello se debe principalmente a eventos reproductivos, más que a facilidades de alimento o protección contra depredadores.…”
Section: Discussionunclassified
“…En particular, Speed et al (2011) sugieren que esta fidelidad se presenta a través del tiempo, e incluso en grandes sistemas arrecifales continuos, proponiendo que ello se debe principalmente a eventos reproductivos, más que a facilidades de alimento o protección contra depredadores. Así mismo, Whitney et al (2012) registraron alta filopatría de la especie con múltiples recapturas fotográficas de un mismo ejemplar en un mismo sitio hasta por siete años, y documentando mayor filopatría en las hembras que en los machos.…”
Section: Discussionunclassified
See 1 more Smart Citation